Correction to: Culture of mesenchymal stem cells derived from equine synovial membrane in alginate hydrogel microcapsules (Stem Cell Research and Therapy (2018) - Santos, Vitor Hugo [UNESP]; Pfeifer, João Pedro Hübbe [UNESP]; De Souza, Jaqueline Brandão [UNESP]; Milani, Betsabéia Heloisa Gentilha [UNESP]; De Oliveira, Rogério Antonio [UNESP]; Assis, Marjorie Golim [UNESP]; Deffune, Elenice [UNESP]; Moroz, Andrei [UNESP]; Alves, Ana Liz Garcia [UNESP] (Springer Nature, 2018)
The original article [1] contained a minor error regarding the mean diameter of the alginate microcapsules described in relation to Fig. 4 in the Results section. The microcapsules had an actual mean diameter of 3000 μm instead of 1000 μm as mistakenly mentioned in the original article.